We built this city Paris - Llewellyn-Jones, Jeremy (Princeton, NJ : Films for the Humanities & Sciences, 2004)
Investigates the crucial role engineering has played in the two-thousand year history of the French capital. Eugene Houseman spearheaded the evolution of Paris in the late 18th century, producing the infrastructure, wide boulevards, and grand buildings that give the city its singular charm. Top French historians, engineers, and archaeologists analyze his work as well as the complex feats of the pre-Houseman years, from the construction of King Philippe's wall and the innovative methods of purifying the Seine in the 13th century to the "revolt of the dead" in 1785. The program also examines the existing Parisian structures at the time of the French Revolutio
Keywords: Paris (France) -- Buildings, structures, etc; Paris (France) -- Description and travel; Paris (France) -- History